Personalized medicine in glaucoma management - A. N. Zhuravleva; O. A. Kiseleva; M. O. Kirillova (Российский офтальмологический журнал, 2019)
The review addresses the management of primary glaucoma as a socially significant multifactorial disease. The main reasons that impede the timely diagnosis and treatment of patients with glaucoma are indicated: blurring of boundaries, conventionality of standards, and lack of individualized approach to treatment. The main risk factors for the development of glaucoma are highlighted, with special attention to hereditary predisposition and the role of “medicine of the future” in managing glaucoma. Four fundamental principles are described: personalization, prediction, prevention and participative attitude (P4 medicine). Advanced scientific understanding of the key risk factors for the development and progression of glaucoma, together with a modern personalized and personified approach will further develop precise individual strategies for the prevention and treatment of the disease.